2014
DOI: 10.1186/1756-3305-7-107
|View full text |Cite
|
Sign up to set email alerts
|

Trematode infections in cattle in Arumeru District, Tanzania are associated with irrigation

Abstract: BackgroundThe relationship between the environment and infection of cattle with trematodes was studied at Arumeru District, Arusha Region, northern Tanzania. Randomly selected villages were grouped into three cattle management strata, (i) zero-grazing (ZZ) (ii) communal grazing without irrigation (ZC) and (iii) communal grazing with irrigation (ZCI).MethodsFaecal samples were collected from 241 cattle, and processed using the Flukefinder® method. Snail intermediate hosts were collected with a snail scoop from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
39
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 17 publications
11
39
2
3
Order By: Relevance
“…This seasonality is in agreement with other investigators who suggested that heavy mortality as a result of fasciolosis occurred during the dry season [49,51]. Cattle grazing in irrigation areas are most susceptible to infection [39].…”
Section: Climate Factorssupporting
confidence: 81%
See 2 more Smart Citations
“…This seasonality is in agreement with other investigators who suggested that heavy mortality as a result of fasciolosis occurred during the dry season [49,51]. Cattle grazing in irrigation areas are most susceptible to infection [39].…”
Section: Climate Factorssupporting
confidence: 81%
“…Liver fluke transmission is dependent on the presence of its snail intermediate host so distribution of the parasite is limited to geographic areas where the appropriate snail species is present [39]. A high prevalence of fasciolosis has been shown towards the end of the dry season and the early part of the rainy season [21,41].…”
Section: Climate Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropical fasciolosis due to F. gigantica Cobbold 1855 has been reported in several parts of Africa , Phiri et al, 2005a, Abebe et al,2010, Nzalawahe et al, 2014 and is likely to be a problem throughout the continent.…”
Section: Epidemiology Of Bovine Fasciolosis In Nigeriamentioning
confidence: 99%
“…The convergence of cattle in common graze land during dry season as well as irrigation practices has been implicated in high prevalence of paramphistomosis (Nzalawahe et al, 2014). In a cross-sectional study in Ethiopia, 51.8% of cattle slaughtered were positive for paramphistomosis with peak prevalence rates observed during October to November (Ayalew et al, 2016).…”
Section: Epidemiology Bovine Paramphistomosis In Nigeriamentioning
confidence: 99%